Kinetics of renal function during induction in newly diagnosed multiple myeloma: Results of two prospective studies by the german myeloma study group dsmm - Bachmann, Friederike; Schreder, Martin; Engelhardt, Monika; Langer, Christian; Wolleschak, Denise; Muegge, Lars Olof; Duerk, Heinz; Schaefer-Eckart, Kerstin; Blau, Igor Wolfgang; Gramatzki, Martin; Liebisch, Peter; Grube, Matthias; et al. (Cancers, 2021)
Background: Preservation of kidney function in newly diagnosed (ND) multiple myeloma (MM) helps to prevent excess toxicity. Patients (pts) from two prospective trials were analyzed, pro-vided postinduction (PInd) restaging was performed. Pts received three cycles with bortezomib (btz), cyclophosphamide, and dexamethasone (dex; VCD) or btz, lenalidomide (len), and dex (VRd) or len, adriamycin, and dex (RAD). The minimum required estimated glomerular filtration rate (eGFR) was >30 mL/min. We analyzed the percent change of the renal function using the International Myeloma Working Group (IMWG) criteria and Kidney Disease: Improving Global Outcomes (KDIGO)-defined categories. Results: Seven hundred and seventy-two patients were eligible. Three hundred and fifty-six received VCD, 214 VRd, and 202 RAD. VCD patients had the best baseline eGFR. The proportion of pts with eGFR <45 mL/min decreased from 7.3% at baseline to 1.9% PInd (p < 0.0001). Thirty-seven point one percent of VCD versus 49% of VRd patients had a decrease of GFR (p = 0.0872). IMWG-defined “renal complete response (CRrenal)” was achieved in 17/25 (68%) pts after VCD, 12/19 (63%) after RAD, and 14/27 (52%) after VRd (p = 0.4747). Conclusions: Analyzing a large and representative newly diagnosed myeloma (NDMM) group, we found no difference in CRrenal that occurred independently from the myeloma response across the three regimens. A trend towards deterioration of the renal function with VRd versus VCD may be explained by a better pretreatment “renal fitness” in the latter group.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Bortezomib; Induction regimen; Kidney; Lenalidomide; Multiple myeloma; Renal failure